Resposta :
Resposta:
Explicação passo-a-passo:
(x+5.(x-4)=x+16
x²-4x+5x -20=x+16
x²+x-x=16+20
x²=36
x=√36
x=6
Resposta:
[tex] \times = \sqrt{46}. \times = - \sqrt{46} [/tex]
Explicação passo-a-passo:
axpandir:
[tex] { \times }^{2} + \times - 20 = \times + 26[/tex]
adicionar 20 a ambos os lados:
[tex] { \times }^{2} + \times - 20 + 20 = \times + 26 + 20[/tex]
simplificar:
[tex] { \times }^{2} + \times = \times + 46[/tex]
subtrair X de ambos os lados:
[tex] { \times }^{2} + \times - \times = \times + 46 - \times [/tex]
simplificar:
[tex] { \times }^{2} = 46[/tex]
resultado correto:
[tex] \times = \sqrt{46}. \times = - \sqrt{46} [/tex]
espero ter te ajudado☺
tenha uma boa noite e bons estudos
